2015
DOI: 10.1515/jped-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of story mapping on third-grade students with Attention Deficit Hyperactivity Disorder

Abstract: The purpose of this study was to examine the effects of story mapping on the reading comprehension scores, on-task behaviors, and attitudes of third- -grade students (N = 6) with ADHD. Students’ reading grade equivalencies were assessed before and after the study. The teacher-researcher compared two other achievement measures before and during story mapping to assess growth. The practical difference in scores as calculated with Cohen’s d revealed that story mapping was successful in improving students’ compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…The results of this study are in line with the outcomes of the studies of Okari [29], Allo et al [1], Chavez et al [57], Tabatabaei and Radi [72], and Boulineau et al [73], all of which revealed the significant effects of using story mapping in teaching writing skills.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study are in line with the outcomes of the studies of Okari [29], Allo et al [1], Chavez et al [57], Tabatabaei and Radi [72], and Boulineau et al [73], all of which revealed the significant effects of using story mapping in teaching writing skills.…”
Section: Discussionsupporting
confidence: 89%
“…The most graphic organizer used in investigating its effect on EFL students' writing development is the mind-mapping technique. Recently, Suprayogi et al [50], Indrawati [51], Usman et al [52], Fu et al [45], Latifah [53], Cope et al [47], Berendsen et al [54], Ynda et al [55], Yuliana [56], Chavez et al [57], Boon et al [58], and Johana [59] investigated the effect, the role, the significance of story mapping in developing, improving, and promoting EFL students' writing skills and abilities in writing all kinds of composition and essay (narrative, descriptive argumentative, expository, cause and effect, and analytical). The selection of the mind mapping technique in this study was based on its positive significance on students' writing performance.…”
Section: Writing Hortatory Expositionmentioning
confidence: 99%
“…Grafik örgütleyiciler, yazma eğitiminde temelde fikir üretmek, üretilen fikirleri bağlamsallaştırmak ve düzenlemek için kullanılan eğitsel araçlardır. Birçok araştırmada yazma becerilerini geliştirmeye katkı sağladığı ortaya konulan (Beydoğan, 2011;Hart, 2020;Sidekli, 2013;Ibnian, 2010;Maltepe & Gültekin, 2020;Kurniawan vd., 2020;Tağa, 2013;Uysal & Sidekli, 2020) bu araçlar; yazma öncesi planlama sürecinde, türe özgü yazma becerilerinin geliştirilmesinde ve özetleme çalışmalarında yaygın olarak işe koşulmaktadır.…”
Section: A E-grafik öRgütleyicilerunclassified